Physician decision making in selection of second‐line treatments in immune thrombocytopenia in children. Issue 7 (6th May 2018) - Grace, Rachael F.; Despotovic, Jenny M.; Bennett, Carolyn M.; Bussel, James B.; Neier, Michelle; Neunert, Cindy; Crary, Shelley E.; Pastore, Yves D.; Klaassen, Robert J.; Rothman, Jennifer A.; Hege, Kerry; Breakey, Vicky R.; et al.
Abstract: Immune thrombocytopenia (ITP) is an acquired autoimmune bleeding disorder which presents with isolated thrombocytopenia and risk of hemorrhage. While most children with ITP promptly recover with or without drug therapy, ITP is persistent or chronic in others. When needed, how to select second‐line therapies is not clear. ICON1, conducted within the Pediatric ITP Consortium of North America (ICON), is a prospective, observational, longitudinal cohort study of 120 children from 21 centers starting second‐line treatments for ITP which examined treatment decisions. Treating physicians reported reasons for selecting therapies, ranking the top three. In a propensity weighted model, the most important factors were patient/parental preference (53%) and treatment‐related factors: side effect profile (58%), long‐term toxicity (54%), ease of administration (46%), possibility of remission (45%), and perceived efficacy (30%). Physician, health system, and clinical factors rarely influenced decision‐making. Patient/parent preferences were selected as reasons more often in chronic ITP (85.7%) than in newly diagnosed (0%) or persistent ITP (14.3%, P  = .003). Splenectomy and rituximab were chosen for the possibility of inducing long‐term remission ( P  < .001). Oral agents, such as eltrombopag and immunosuppressants, were chosen for ease of administration and expected adherence ( P  < .001). Physicians chose rituximab in patients with lower expected adherence ( P  = .017). Treatment choice showed some physician and treatment center bias. This study illustrates the complexity and many factors involved in decision‐making in selecting second‐line ITP treatments, given the absence of comparative trials. It highlights shared decision‐making and the need for well‐conducted, comparative effectiveness studies to allow for informed discussion between patients and clinicians.